2016
DOI: 10.18805/ijar.11466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selection for body weight in Japanese quails(Coturnix coturnix Japonica) on some production traits

Abstract: The aim of the study was to identify quails which have different body weight for some production traits such as egg production, egg characteristics, daily feed consumption and feed conversion ratio (FCR). The selection was based on body weight in Japanese quail over two generations using 150 quails (120 female and 30 male). These groups consisted of Low Body Weight (LBW), High Body Weight (HBW) and control. Average body weights for females at the end of five weeks were 182.3±0.5, 159.5±0.34, and 141.7±0.55 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
2
18
2
1
Order By: Relevance
“…Warren (1930) indicated that in crosses between males having the gene for fast-feathering rate and females having the gene for slow-feathering rate, gender may be detected by the extent of growth in primary and secondary wing feathers at 1 day old and by the existence or absence of tail feathers at 10 days old. Females have been reported to have significantly higher feather weight (Wecke et al, 2017) and heavier BW (Taskin et al, 2017) than males across generations.…”
Section: Introductionmentioning
confidence: 99%
“…Warren (1930) indicated that in crosses between males having the gene for fast-feathering rate and females having the gene for slow-feathering rate, gender may be detected by the extent of growth in primary and secondary wing feathers at 1 day old and by the existence or absence of tail feathers at 10 days old. Females have been reported to have significantly higher feather weight (Wecke et al, 2017) and heavier BW (Taskin et al, 2017) than males across generations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there were significant higher BW's favoring the selected line, however, the selected line had significantly higher BW1 than the CL (Narendra Nath et al, 2011). Regardless of generation, selected lines for BW had significantly heavier BW35 than the control line (Taskin et al, 2017).…”
Section: Line Effects On Growth Traitsmentioning
confidence: 93%
“…In addition, there was significant sexual dimorphism of Japanese quail BW favoring females than its counterpart males which occurred as a result of male sexual activities due to the hormonal change. Similarly, Taskin et al (2017) indicated that sex was a significant source of variation for BW at all the ages across selection generations. Similarly, calculated GR1-35 indicated that females had faster GR than males (Daikwo et al, 2014).…”
Section: Sex Effects On Growth Traitsmentioning
confidence: 97%
“…At 38 weeks of age, the average body weights of male and female quails were 109.38g and 117.92g respectively. Taskin et al (2017) showed that quails of different weight had the following differences: Significant differences were observed for total egg production and egg width for Group X Generation's interactions.…”
Section: According To Fig 1 Body Weight Of All Three Species Increasmentioning
confidence: 99%